Structural health monitoring and engineering structures select proceedings of SHM&ES 2020 - Tanda, Maria Giovanna; Chiapponi, Luca (Lecture Notes in Civil Engineering, 2021)
The book presents the select proceedings of International Conference on Structural Health Monitoring and Engineering Structures (SHM&ES) 2020. It brings together different applied and technological aspects of structural health monitoring. The main topics covered in this book include damage assessment, structural health monitoring, engineering fracture mechanics, Inverse problem using optimization techniques, machine learning, deep learning, Artificial intelligent and non-destructive evaluation. It will be a reference for professionals and students in the areas of civil engineering, applied natural sciences and engineering management.